The hound of death - Christie, Agatha (HarperCollinsPublishers, 2016)
A collection of macabre mysteries, including the superlative story The Witness for the Prosecution... Twelve unexplained phenomena with no apparent earthly explanation... A dog-shaped gunpowder mark; an omen from 'the other side'; a haunted house; a chilling seance; a case of split personalities; a recurring nightmare; an eerie wireless message; an elderly lady's hold over a young man; a disembodied cry of 'murder'; a young man's sudden amnesia; a levitation experience; a mysterious SOS. To discover the answers, delve into the supernatural storytelling of Agatha Christie.